The Relationship Between Pastoral Care and The Anxiety Level of Preoperative Patients at Santa Elisabeth Hospital Medan: Anxiety Level of Preoperative Patients - Telaumbanua, Fitriani; Barus, Mardiati; Derang, Imelda; Simanullang, Murni Sari Dewi (STIKes Mandala Waluya Kendari, 2024)
Background: Anxiety is restlessness and helplessness, especially when illness occurs after surgery, and supports pastoral care to help patients be comfortable and at ease. The aim of study was to determine the relationship between pastoral care and anxiety levels in preoperative patients at Hospital Santa Elisabeth Medan. Methods: The Methods of research is a quantitative and cross-sectional study. The population of this study was all preoperative subjects. The sample size was 71 people. The research instrument is the APAIS questionnaire (Amsterdam Preoperative Anxiety and Information Scale). The Amsterdam Preoperative Information and Anxiety Scale (APAIS) is one of the designs designed to assess the causes of anxiety before the operation, a tool was created to warn workers to assess the individual's risk. Results: The results showed that most of the recipients of pastoral care were in the good category (90.1%) and the majority in the emergency category (49.3%). Data analysis used Spearman's rank test for univariate and bivariate variables. Conclusion Spearman's level statistical test (rho) showed a value of r = (0.520) and the strength of the relationship resulted in a significant p-value = 0.000(p <0.05). Conclusions: The conclusion of this study is expressed that there's a relationship between peaceful bolster and uneasiness levels of patients some time recently surgery at Santa Elisabeth Clinic Medan and great peaceful care can diminish anxiety levels in patients who will experience surgery.